ChemInform Abstract: Stereoselective Cascade Double‐Annulations Provide Diversely Ring‐Fused Tetracyclic Benzopyrones. Issue 17 (4th April 2013) - Baskar, Baburaj; Wittstein, Kathrin; Sankar, Muthukumar G.; Khedkar, Vivek; Schuermann, Markus; Kumar, Kamal
Abstract The presented new annulation strategy provides stereoselective access to complex tetracyclic benzopyrones.